2003
DOI: 10.1037/0894-4105.17.3.402
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory in schizophrenia: An examination of the distribution of memories.

Abstract: Patients with schizophrenia display numerous memory impairments. Examination of autobiographical memory distribution across the life span can constrain theories of how schizophrenia affects memory. Previously, schizophrenic patients were shown to produce fewer memories from early adulthood than from childhood or the recent past (A. Feinstein, T. E. Goldberg, B. Nowlin, & D. R. Weinberger, 1998), this temporal paucity corresponding with illness onset. The current study examined this issue further using a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
27
0
2

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 51 publications
7
27
0
2
Order By: Relevance
“…In contrast, the early component of the reminiscence bump concerning social identity, and corresponding mainly to memories of public events, seemed relatively preserved. These results are consistent with previous evidence that autobiographical memory impairments of patients diagnosed with schizophrenia are particularly marked in late adolescence and early adulthood (Elvevag et al, 2003;Feinstein et al, 1998;Riutort et al, 2003). In keeping with the proposal that impaired personal identity is a fundamental disturbance in schizophrenia (Bleuler, 1911;Jaspers, 1963), suggest that this illness is associated with an impairment of autobiographical memories of events that had occurred during the last stage of personal identity development.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, the early component of the reminiscence bump concerning social identity, and corresponding mainly to memories of public events, seemed relatively preserved. These results are consistent with previous evidence that autobiographical memory impairments of patients diagnosed with schizophrenia are particularly marked in late adolescence and early adulthood (Elvevag et al, 2003;Feinstein et al, 1998;Riutort et al, 2003). In keeping with the proposal that impaired personal identity is a fundamental disturbance in schizophrenia (Bleuler, 1911;Jaspers, 1963), suggest that this illness is associated with an impairment of autobiographical memories of events that had occurred during the last stage of personal identity development.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, they recall few specific autobiographical memories (Riutort et al, 2003). The deficit of autobiographical memories is particularly marked in late adolescence and early adulthood (Elvevag et al, 2003;Feinstein et al, 1998;Riutort et al, 2003). Recently, conscious awareness associated with autobiographical memory has been investigated in schizophrenia (Danion et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since AM can cover the entire lifespan from childhood to recent life, many studies on AM in other psychiatric or neurological diseases have investigated the temporal gradient pattern of AM [5,[12][13][14] , which we still do not know for BD. It is strongly suspected that BD patients with a large number of episodes or long duration of illness might show severer impairments in AM.…”
Section: Introductionmentioning
confidence: 99%
“…Autobiographical memory recall is compromised in schizophrenia (e.g., Elvevåg et al, 2003;Riutort et al, 2003;Danion et al, 2005;McLeod et al, 2006;Cuervo-Lombard et al, 2007;D'Argembeau et al, 2008) with recent findings suggesting that recollection of negative autobiographical events is particularly affected (Neumann et al, 2007;MacDougall et al, unpublished results). It has been suggested that an impoverished autobiographical memory may hinder the ability to think in more complex ways about oneself or others (Dimaggio et al, 2012).…”
Section: Introductionmentioning
confidence: 73%